2015
DOI: 10.3325/cmj.2015.56.14
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of four international cardiovascular disease prediction models and the prevalence of eligibility for lipid lowering therapy in HIV infected patients on antiretroviral therapy

Abstract: AimTo compare four cardiovascular disease (CVD) risk models and to assess the prevalence of eligibility for lipid lowering therapy according to the 2013 American College of Cardiology/American Heart Association (ACC/AHA) guidelines, European AIDS Clinical Society Guidelines (EACS), and European Society of Cardiology and the European Atherosclerosis Society (ESC/EAS) guidelines for CVD prevention in HIV infected patients on antiretroviral therapy.MethodsWe performed a cross-sectional analysis of 254 consecutive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
9
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 44 publications
3
9
0
1
Order By: Relevance
“…This finding is consonant with the lack of measurement of CVD risk factors. The higher proportion with an indication for statin therapy by ASCVD relative to FRS guidelines has also been reported among other HIV patient populations [ 19 , 20 ]. Yet, there was high agreement between ASCVD and FRS in our cohort as has been reported in other small clinical HIV-cohorts [ 21 ].…”
Section: Discussionmentioning
confidence: 65%
“…This finding is consonant with the lack of measurement of CVD risk factors. The higher proportion with an indication for statin therapy by ASCVD relative to FRS guidelines has also been reported among other HIV patient populations [ 19 , 20 ]. Yet, there was high agreement between ASCVD and FRS in our cohort as has been reported in other small clinical HIV-cohorts [ 21 ].…”
Section: Discussionmentioning
confidence: 65%
“…Other studies have reported moderate or low concordance in CVD risk score stratification among risk prediction equations [3638]. The HOPS cohort had a higher prevalence of overweight or obese participants than that reported in other HIV-infected populations to which the risk prediction equations have been applied [18, 19, 37, 38]. The HOPS cohort may have differed from these other populations in additional important ways, including by sociodemographic and insurance status, or healthcare-seeking behaviors that we could not assess.…”
Section: Discussionmentioning
confidence: 99%
“…A study from the Netherlands reported that around 33% of HIV patients measured by FRS had a high risk of cardiovascular disease (Krikke et al, 2016). This was supported by a cross-sectional study conducted in Croatia (n = 254) reporting that people with HIV had a high risk of CVD, ranging from 27.2% measured by FRS to 51.6% for DAD scores (Begovac et al, 2015). A study from Zimbabwe in HIV-positive people (n = 215, mean age = 39.8-42.0, under ART 3.9 (SD = 3.4)) also reported 1.4% prevalence of high risk cardivascular disease in the next ten years (Zhou et al, 2015).…”
Section: Discussionmentioning
confidence: 62%